THE FORMULATION OF MINIMUM WAGE (MW) IN THE LIGHT OF MAQASHID AL-SHARIA: INDONESIAN CASE - Yulizar D Sanrego (Share: Jurnal Ekonomi dan Keuangan Islam, 2017)
Minimum Wage (MW) is a policy set by the government as a basis reference at labor market for every company to pay their workers wages. Since workers always have a low bargaining position when dealing with employers in the determination of their wage rates, therefore the MW could becomes the safety net for workers to have "decent living" when he began to enter the world of work. In the case of Indonesia, the formulation of WM is referring to the parameters of Decent Living Needs (DLN) according to the Ministry of Manpower Decree No. 13, the year 2012. There are at least seven components in order to formulate MW within the DLN Framework, namely: (1) food and beverages, (2) clothing/apparel (3) housing, (4) education, (5) health, (6) transportation and (7) recreation and savings. Meanwhile, in Islam, every transaction made must be ensured preserve and achieve maqashid al sharia (sharia objectives): (1) religion/faith, (2) life, (3) intellect, (4) posterity, and (5) property. Using content analysis, the paper indicates that the regulation above is relevant to the conditions and objectives of sharia-based wage system (maqashid sharia). The Decent Living Needs (DLN)-based minimum wage setting which operated in the 60 components meet the basic needs components of the workers for their daily life which includes the needs of education, health, recreation, and saving. Hence, another challenge in relation to the DLN is how to ensure that the purchasing power of labor for their shelter within the existing MW formulation. What kind of shelter that considered as al dharuriyah within the existing MW setting. Therefore, there is a call for synergy between the government and the housing industry that can offer shelter in accordance with the purchasing power of labor with the existing level of MW and feasible within the framework of DLN so that might be considered as social policy elements. =========================================== Formulasi Upah Minimum dalam Perspektif Maqashid Syariah di Indonesia_______________________________________________ Upah Minimum (UM) merupakan kebijakan yang ditetapkan pemerintah sebagai dasar acuan di pasar tenaga kerja bagi setiap perusahaan. Pekerja dihadapkan pada posisi tawar yang rendah ketika berhadapan dengan pengusaha dalam penentuan tingkat upah mereka, oleh karena itu UM bisa menjadi jaring pengaman bagi pekerja untuk memiliki "kehidupan yang layak" ketika ia mulai memasuki dunia kerja. Dalam kasus Indonesia, perumusan UM mengacu pada parameter Kebutuhan Hidup Layak sesuai dengan Keputusan Menteri Tenaga Kerja Nomor 13, tahun 2012. Setidaknya, ada tujuh komponen perumusan MW dalam Kebutuhan Hidup Layak, yaitu: (1) makanan dan minuman, (2) pakaian / pakaian (3) perumahan, (4) pendidikan, (5) kesehatan, (6) transportasi dan (7) rekreasi dan tabungan. Sementara itu, dalam Islam setiap transaksi yang dilakukan harus dipastikan melestarikan dan mencapai maqashid al syariah (tujuan syariah): (1) agama / iman, (2) hidup, (3) kecerdasan, (4) anak cucu, dan (5) properti. Hasil analisa menunjukkan bahwa Keputusan Menteri Tenaga Kerja Nomor 13, tahun 2012 relevan dengan kondisi dan tujuan dari sistem upah berbasis syariah (maqashid syariah). Kebutuhan Hidup Layak berbasis penetapan upah minimum yang beroperasi di 60 komponen, memenuhi kebutuhan komponen dasar para pekerja untuk kehidupan mereka sehari-hari. Kebetuhan tersebut meliputi kebutuhan pendidikan, kesehatan, rekreasi dan tabungan. Tantangan yang harus dihadapi ialah bagaimana memastikan bahwa daya beli tenaga kerja dan jaminan tempat tinggal mereka dalam perumusan UM. Apa jenis hunian yang dianggap sebagai al dharuriyah dalam pengaturan UM yang ada. Oleh karena itu, diperlukan sinergisitas antara pemerintah dan industri perumahan dalam menawarkan perumahan sesuai dengan daya beli tenaga kerja dengan tingkat upah minimum sebagai elemen kebijakan sosial.